Test your emotional intelligence - "Wood, Robert" (New Delhi, 2003)
It takes more than just a high intelligence quotient (IQ) to be successful-a high emotional intelligence quotient (EQ) is now recognized as being of equal importance. As a result, employers are increasingly seeking evidence of it through the use of an EQ test. But what is EQ and how do you assess it? This book aims to provide you with a thorough understanding of emotional intelligence. It provides you with examples of the types of question typically used in EQ tests, and also a simple method of assessing your own EQ once you have completed the questions. The practice questions are devised to test aspects of the five key components of emotional intelligence:-Self-awareness-Self-regulation-Empathy-Motivation-Social Skills
Keywords: Emotional intelligence